(untitled) (The International Journal for Scientific Research, 2024)
Crisis forecasting is one of the important sciences in management sciences, especially within the scope of small and medium enterprises, because it is more affected than others as a result of their limited financial, administrative and human capabilities. Given this importance, this study aimed to measure the role of crisis forecasting in avoiding obstacles and risks for small and medium enterprises in... Al Rawdah District - Kingdom of Saudi Arabia. In order for the researcher to be able to verify the study hypotheses and achieve its objectives, she followed the descriptive analytical approach, in its social survey style. She also relied in her study on the questionnaire, which was built via the Google Drive forms application for the purpose of sending it via an electronic link to a sample. An amount of 178 individuals are owners and managers of these establishments. The researcher also used the SPSS application to conduct statistical tests to ensure the integrity of the questionnaire, as well as to calculate the impact and statistical differences. The study concluded: - There is a statistically significant role at the significance level of 0.05 for predicting crises and avoiding obstacles and risks. - There are no statistically significant differences at the significance level of 0.05 between the averages of the sample’s answers, whether regarding predicting crises, or avoiding obstacles and risks, which is attributed to the personal variables of the study. The study also presented many recommendations, most notably: Small and medium enterprises in the Qassim region must prepare a reserve staff to avoid their staff from stopping work, in order to ensure business continuity in the event that workers stop working.